Differential Expression Pattern of Retroviral Envelope Gene in the Equine Placenta - Stefanetti, Valentina; Pascucci, Luisa; Wilsher, Sandra; Cappelli, Katia; Capomaccio, Stefano; Reale, Lara; Passamonti, Fabrizio; Coletti, Mauro; Crociati, Martina; Monaci, Maurizio; Marenzoni, Maria Luisa (Frontiers in Veterinary Science, 2021)
Endogenous retroviruses (ERVs) are proviral phases of exogenous retroviruses, which have coevolved with vertebrate genomes for millions of years. The conservation of ERV genes throughout evolution suggests their beneficial effects on their hosts’ survival. An example of such positive selection is demonstrated by the syncytin gene, which encodes a protein with affinity for various mammalian placentas that is involved in the formation of syncytiotrophoblasts. Although the horse has an epitheliochorial placenta, in which the fetal trophoblasts are simply apposed to the intact uterine epithelium, we have previously demonstrated that the equine ERV (EqERV) env RNA is unexpectedly expressed in placental tissue. In the present study, we investigated the expression pattern of the EqERV env gene in different parts of the equine placenta, to gain more insight into its putative role in the fetal–maternal relationship. To this end, we used reverse transcription–quantitative PCR (RT–qPCR) and in situ hybridization assays to analyze different target areas of the equine placenta. The retroviral env gene is expressed in the equine placenta, even though there is no syncytium or erosion of the uterine endometrium. The gene is also expressed in all the sampled areas, although with some quantitative differences. We suggest that these differences are attributable to variations in the density, height, and degree of morphological complexity of the chorionic villi forming the microcotyledons. The involvement of the EqERV env gene in different functional pathways affecting the fetus–mother relationship can be hypothesized.